Effective removal of nickel(II) and zinc(II) in mono-compound and binary systems from aqueous solutions by application of alginate-based materials. Issue 9 (15th July 2023) - Benettayeb, A.; Guibal, E.; Bhatnagar, A.; Morsli, A.; Kessas, R.
ABSTRACT: In the present study, beads of alginate, alginate-biuret and alginate-urea, were synthesised for the removal of Ni(II) and Zn(II) metal ions from aqueous solution (in single and in the bimetallic component solution). The properties of the synthesised sorbents were investigated by pHpcz, ESEM-EDX and ESEM. The modelling of experimental data demonstrate that the PSORE equation fits well the kinetic profiles, while Langmuir and also Sips models correspond well to the results of sorption isotherms (heterogeneous surface). Also, the spontaneous of process and endothermic nature of sorption was demonstrated by thermodynamic study. The maximum sorption capacity of 3.22, 4.73 and 8.53 mmol g −1 was found for the beads of alginate, alginate-biuret and alginate-urea, respectively, in case of Ni(II) while it was 6.77, 6.97 and 7.14 mmol g −1 for alginate, alginate-biuret and alginate-urea, respectively, in case of Zn(II). It was found that at 0.3 mmol L −1 concentration, Zn(II) was selectively adsorbed while Ni(II) ions were concentrated/enriched in the solution in the case of alginate-urea, but alginate-biuret and alginate beads adsorbed almost the same amount of Ni(II) and Zn(II). In the bimetallic solution, the study of selectivity coefficients (KS ) shows that the alginate-urea is a selective sorbent for Zn(II) and alginate-biuret for Ni(II) ions. Therefore, the two functionalised polysaccharides do not show the same harmony in front of the two-chemical species, thus, giving the possibility of their use as selective adsorbents in solutions containing these elements and can be used in applications of different interest.